Implementasi Algoritma Pproportional Coding pada Sistem Absensi Berbasis Barcode Menggunakan Delphi - Fauziah Fauziah; Aah Sumiah; Andri Indriana Purnama (Universitas Kuningan, 2019)
The development of information technology are accelerating into the various fields, so now more and more companies are trying to increase its business primarily in the areas of business that are intimately associated with the information technology itself. This is supported by the statement that the usefulness of computers in business applications is to provide information quickly and accurately. This information is like blood flowing in the body of an enterprise. If in a company, the information is stalled or blocked, then the system will become a shabby enterprise. With the computer as a data processing tool, then all areas within a company or agency may be computerized, including the use of attendance of employees in a company is one of the important things to know the performance of employees quickly and accurately. To overcome the above authors want to provide a solution by designing and applying a manual workflow attendance system into a more practical application, quickly and precisely. Therefore, the authors tried to implement it manually into the attendance system attendance system based barcode using proportionate coding algorithm as elaboration. Keywords: Proportional Coding, System, Attendance, Barcode, Delphi.